Using Digital Flashcards (DFs) as a Learning Media to Enhance Students’ Speaking Skill - Dhenya Airin Luthfillah; Nur Fauzia (Jetlal, 2023)
The aim of this study was to investigated the effect of using Digital Flashcards (DFs) on improving junior high school students’ speaking skill. This study employed pre-experimental design method in one group pre-test and post-test design. The researcher gathered the data by providing pre-test and post-test which are formulated the sepaking test about describing person. The sample of this study was seventh grade of junior high school in Gresik. The test was tabulated and analyzed by using SPSS 23. The results of this study showed that the use of Digital Flashcards is effective to improve students’ speaking skill in junior high school. It was proven by the result of the data that there was a significant difference between the pre-test and post-test scores. The mean score was 38.15 in the pre-test and 49.57 in the post-test, thus the average found is in the large effect category (0.625). The results also showed significant progress among four criteria assessment by IELTS under investigation, pronunciation (0.629) and lexical resource (0.623) were the most noticebly increased after the treatment of Digital Flashcards. In conclusiom, the current study suggests the Digital Flashcards media can be applied towards junior high school level to improve students’ speaking skill.